1994
DOI: 10.2337/diacare.17.12.1460
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of a Once-Daily Controlled-Release Formulation of Glipizide and Immediate-Release Glipizide in Patients With NIDDM

Abstract: Glipizide-GITS was significantly more effective than immediate-release glipizide in reducing FPG levels. Both formulations reduced postprandial plasma glucose levels equally; however, glipizide-GITS exerted its control in the presence of lower plasma glipizide concentrations in addition to significantly lower insulin and C-peptide levels. This suggests that glipizide-GITS improves insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 3 publications
0
20
0
1
Order By: Relevance
“…Our study has confirmed these findings in showing that once-daily glipizide GITS therapy achieves the same degree of glycemic control as twice-daily administration of immediate-release glipizide despite their markedly different plasma concentration-time profiles. As another study, which was longer in duration, showed significantly lower fasting insulin levels, 9 lower fasting insulin may be the reason why there is no weight gain in long-term studies with glipizide GITS therapy.…”
Section: Comparison Of Extended-and Immediate-release Glipizidementioning
confidence: 89%
“…Our study has confirmed these findings in showing that once-daily glipizide GITS therapy achieves the same degree of glycemic control as twice-daily administration of immediate-release glipizide despite their markedly different plasma concentration-time profiles. As another study, which was longer in duration, showed significantly lower fasting insulin levels, 9 lower fasting insulin may be the reason why there is no weight gain in long-term studies with glipizide GITS therapy.…”
Section: Comparison Of Extended-and Immediate-release Glipizidementioning
confidence: 89%
“…Glipizide sustained release formulation is significantly more effective than the immediate release formulation of glipizide in reducing fasting plasma glucose levels and side effects. 30 Formulation of glipizide as mucoadhesive sustained release dosage form could also exhibit a decrease in side effects.…”
Section: In Vivo Studymentioning
confidence: 99%
“…Glipizide gastrointestinal therapeutic system (GITS), a controlledrelease sulphonylurea, was introduced [5]. A dose of 5 mg was administered for 2 days, then 10 mg; insulin was simultaneously slowly withdrawn over a period of 5 days.…”
mentioning
confidence: 99%